Firm survival and gender of firm owner in times of COVID-19: Evidence from 10 European countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
This paper uses firm level data from the World Bank Enterprise surveys conducted in 2019 and from the COVID-19 follow-up surveys conducted in 2020 in ten European countries to investigate the link between the gender of the firm's owner and firm survival until 2020.The estimated effect of female ownership is positive ceteris paribus after controlling for various firm characteristics that are known to be related to survival. Furthermore, the size of this estimated effect can be considered to be large on average. Having a female owner helped firms to survive.
Keywords: D22; L20; L25; L29; 330; Gender; female owned firms; firm survival; COVID-19; World Bank Enterprise Surveys